Association between Polymorphisms in Antioxidant Genes and Inflammatory Bowel Disease - Costa Pereira, Cristiana (2017)
Inflammation is the driving force in inflammatory bowel disease (IBD) and its link to oxidative stress and carcinogenesis has long been accepted. The antioxidant system of the intestinal mucosa in IBD is compromised resulting in increased oxidative injury. This defective antioxidant system may be the result of genetic variants in antioxidant genes, which can represent susceptibility factors for IBD, namely Crohn's disease (CD) and ulcerative colitis (UC). Single nucleotide polymorphisms (SNPs) in the antioxidant genes SOD2 (rs4880) and GPX1 (rs1050450) were genotyped in a Portuguese population comprising 436 Crohn's disease and 367 ulcerative colitis patients, and 434 healthy controls. We found that the AA genotype in GPX1 is associated with ulcerative colitis (OR = 1.93, adjusted P-value = 0.037). Moreover, we found nominal significant associations between SOD2 and Crohn's disease susceptibility and disease subphenotypes but these did not withstand the correction for multiple testing. These findings indicate a possible link between disease phenotypes and antioxidant genes. These results suggest a potential role for antioxidant genes in IBD pathogenesis and should be considered in future association studies.